STUDY RETURN ON ASSET: THE EFFECT OF DEBT TO EQUITY RATIO AND LONGTERM DEBT TO EQUITY RATIO - Gultom, Dedek Kurniawan; Aulia, Dzaza Dinda; Jufrizen, Jufrizen (International Proceeding of Law and Economic; 2020: International Proceeding of Law and Economic, 2021)
The objectives to be achieved in this study are to determine and analyze the effect of Debt to Equity Ratio (DER) on Return On Assets (ROA), to determine and analyze the effect of Long-term Debt to Equity Ratio (LTDER) on Return On Assets (ROA) and to knowing and analyzing the effect of Debt to Equity Ratio (DER) and Long-term Debt to Equity Ratio (LTDER) on Return On Assets (ROA) at PT. Kemasindo Rapid Medan. This study uses an associative approach. Data collection techniques in this study were carried out using documentation techniques. The data used in this study is quantitative data sourced from secondary data obtained by taking data obtained directly to PT. Kemasindo Rapid Medan. The analysis technique is carried out using multiple linear analysis techniques, classical assumption test, partial and simultaneous hypothesis testing and determination test. Based on the results of research conducted partially between Debt to Equity Ratio to Return on Assets shows a positive relationship but has no effect on Return On Assets at PT. Kemasindo Period 2010-2019. Based on the results of research conducted partially between Long Term Debt to Equity ratio to Debt to Equity Ratio there is no effect on Return On Assets at PT. Kemasindo Period 2010-2019. Based on the results of simultaneous research, Debt to Equity Ratio and Term Debt to Equity Ratio show a positive relationship and have a significant effect on Return On Assets at PT. Kemasindo Period 2010-2019